Electoral violence: An introduction. (January 2020) - Birch, Sarah; Daxecker, Ursula; Höglund, Kristine
Elections are held in nearly all countries in the contemporary world. Yet despite their aim of allowing for peaceful transfers of power, elections held outside of consolidated democracies are often accompanied by substantial violence. This special issue introduction article establishes electoral violence as a subtype of political violence with distinct analytical and empirical dynamics. We highlight how electoral violence is distinct from other types of organized violence, but also how it is qualitatively different from nonviolent electoral manipulation. The article then surveys what we have learned about the causes and consequences of electoral violence, identifies important research gaps in the literature, and proceeds to discuss the articles included in the special issue. The contributions advance research in four domains: the micro-level targeting and consequences of electoral violence, the institutional foundations of electoral violence, the conditions leading to high-stakes elections, and electoral violence in the context of other forms of organized violence. The individual articles are methodologically and geographically diverse, encompassing ethnography, survey vignette and list experiments and survey data, quantitative analyses of subnational and crossnational event data, and spanning Africa, Latin America, and Asia.